Chemical looping glycerol reforming for hydrogen production by Ni@ZrO2 nanocomposite oxygen carriers. (19th July 2018) - Jiang, Bo; Li, Lin; Bian, Zhoufeng; Li, Ziwei; Sun, Yang; Sun, Zhehao; Tang, Dawei; Kawi, Sibudjing; Dou, Binlin; Goula, Maria A.
Abstract: The research describes the synthesis of nanocomposite Ni@ZrO2 oxygen carriers (OCs) and lanthanide doping effect on maintaining the platelet-structure of the nanocomposite OCs. The prepared OCs were tested in chemical looping reforming of glycerol (CLR) process and sorption enhanced chemical looping reforming of glycerol (SE-CLR) process. A series of characterization techniques including N2 adsorption-desorption, X-ray diffraction (XRD), inductively coupled plasma optical emission spectrometry (ICP-OES), high resolution transmission electron microscopy (HRTEM), H2 temperature-programmed reduction (H2 -TPR), H2 pulse chemisorption and O2 temperature-programmed desorption (O2 -TPD) were used to investigate the physical properties of the fresh and used OCs. The results show that the platelet-stack structure of nanocomposite OCs could significantly improve the metal support interaction (MSI), thus enhancing the sintering resistance. The effect of lanthanide promotion on maintaining this platelet-stack structure increased with the lanthanide radius, namely, La 3+  > Ce 3+  > Pr 3+  > Yb 3+ . Additionally, the oxygen mobility was also enhanced because of the coordination of oxygen transfer channel size by doping small radius lanthanide ions. The CeNi@ZrO2 showed a moderate 'dead time' of 220 s, a high H2 selectivity of 94% and a nearly complete glycerol conversion throughout a 50-cycle CLR test. In a 50-cycle SE-CLR stability test, the CeNi@ZrO2 CaO showed high H2 purity of 96.3%, and an average CaCO3 decomposition percentage of 53% without external heating was achieved. Graphical abstract: Image 1 Highlights: Nanocomposite oxygen carriers were synthesized and first applied in CLR and SE-CLR. The lanthanide doping could improve oxygen mobility and thermal stability. A H2 purity of 95.3% and a CaCO3 regeneration percentage without external heating of 53% were reached.